1997
DOI: 10.1063/1.120528
|View full text |Cite
|
Sign up to set email alerts
|

Composition evaluation of InxGa1−xAs Stranski-Krastanow-island structures by strain state analysis

Abstract: The compositional analyses of InxGa1−x/GaAs (001) island structures grown by molecular beam epitaxy at a substrate temperature of 560 °C with nominal In contents of x=60% and 100% are presented on the basis of high resolution transmission electron microscopy micrographs. The linear dependence of the lattice parameter on the In content (Vegard’s law) is exploited to quantitatively derive composition profiles on an atomic scale by measuring local lattice parameters and displacements. The relaxation of the thin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 10 publications
1
65
1
Order By: Relevance
“…In literature, strain fields in and around the InAs QD's have been suggested. 1,8,[18][19][20] It is interesting to note that the experimentally found width of the base of the pyramids ͑ϳ10 nm͒ is able to accommodate one unit cell more of GaAs than InAs. If the strain is relieved via misfit dislocations, this would result in two GaAs half-planes per QD.…”
Section: Strain Fieldsmentioning
confidence: 99%
“…In literature, strain fields in and around the InAs QD's have been suggested. 1,8,[18][19][20] It is interesting to note that the experimentally found width of the base of the pyramids ͑ϳ10 nm͒ is able to accommodate one unit cell more of GaAs than InAs. If the strain is relieved via misfit dislocations, this would result in two GaAs half-planes per QD.…”
Section: Strain Fieldsmentioning
confidence: 99%
“…In most growth processes, nonuniform Ga incorporation in nominally InAs QDs has been reported. 2,3,4,5,6,7,8,9,10,11,12,13,14,15,16 Photoluminescence studies of annealed QDs have shown a blue-shift of their emission line, 5,6,17,18,19 which was suggested to reflect diffusion of Ga atoms from the matrix material into the QD during annealing. However, it is not clear to which extent the blue-shift is a consequence of chemical substitution (bulk GaAs has a wider band gap than InAs), and to which extent it is due to reduced strain in the QD after Ga interdiffusion, which also causes a band-gap widening.…”
Section: Introductionmentioning
confidence: 99%
“…5,18,19 There is much experimental evidence in support of position-dependent compositions in various QDs. 7,15,16,18 Rosenauer et al 7 evaluated the composition of In x Ga 1−x As/ GaAs QD structure by measuring local lattice parameters and displacements assuming a linear dependence of the lattice parameter on the In content ͑Vegard's law͒. Chu and Wang 20 and Duan et al 21 analyzed the strain fields for QD structures with a nonuniform composition, and showed that the strain fields are not uniform in the QD.…”
Section: Introductionmentioning
confidence: 99%
“…5 Many theoretical and experimental investigations have been conducted to understand how different growth parameters influence the size, shape, and composition of alloyed QDs, in the hope that such understanding will allow better control of their electronic properties. [5][6][7][8][9][10][11][12][13][14][15][16] A recent literature review 17 suggests that no existing theory can predict the complicated interdependence of QD shape, strain, and composition. Moreover, if a QD island grows sufficiently large, it will eventually induce strain-relieving misfit dislocations.…”
Section: Introductionmentioning
confidence: 99%